2021
DOI: 10.1177/2473974x211009830
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Tertiary Rhinology Care Utilization

Abstract: Objective The objective of this study was to determine the impact of patient demographics and socioeconomic factors on the utilization of tertiary rhinology care services in an upper Midwestern academic medical center. Study Design Retrospective review of electronic health records. Setting Academic medical center. Methods The electronic health record of our academic center was interrogated for the demographics and diagnosis of chronic rhinosinusitis (CRS) among adult patients seen by fellowship-trained rhinolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Vamosi et al reported that nonwhite patient groups were associated with higher no‐show rates in voice therapy likely due to transportation availability and differences in income and education 22 . A previous study from our group found areas with the highest Black populations in our care network had lower median income and education levels and correspondingly lower utilization rates for tertiary rhinology services 23 . This highlights the importance of understanding contributing factors in adherence and compliance to therapy recommendations in addition to equitable access to specialty care.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Vamosi et al reported that nonwhite patient groups were associated with higher no‐show rates in voice therapy likely due to transportation availability and differences in income and education 22 . A previous study from our group found areas with the highest Black populations in our care network had lower median income and education levels and correspondingly lower utilization rates for tertiary rhinology services 23 . This highlights the importance of understanding contributing factors in adherence and compliance to therapy recommendations in addition to equitable access to specialty care.…”
Section: Discussionmentioning
confidence: 61%
“… 22 A previous study from our group found areas with the highest Black populations in our care network had lower median income and education levels and correspondingly lower utilization rates for tertiary rhinology services. 23 This highlights the importance of understanding contributing factors in adherence and compliance to therapy recommendations in addition to equitable access to specialty care.…”
Section: Discussionmentioning
confidence: 99%
“…24 Additionally, White individuals are more likely to receive specialist care than minorities. 15,25 Thereafter, as the existing literature largely draws samples from the outpatient specialty care setting, 13,15,24,25 we suspect that increased presentation to high-acuity settings among minorities further contributes to their underrepresentation. Our sample's racial breakdown is unique in that there is a marked overrepresentation of traditionally underrepresented minorities (67.9%) compared to the existing literature that has typically analyzed samples consisting of 70% Whites or greater.…”
Section: Discussionmentioning
confidence: 99%
“…14 Meanwhile, higher income and educational attainment, along with White race, have been associated with increased utilization of outpatient rhinology care for sinusitis, despite having an overall lower incidence among these groups. 5, 15 It is important to note, additionally, that many of the aforementioned studies exhibit limited minority representation, with minorities frequently making up less than 30% of the sample. 12, 13, 15 There is, therefore, a need to study populations with larger minority representation.…”
Section: Introductionmentioning
confidence: 99%
“…This project was approved under our department-wide OTO Clinomics outcomes assessment platform, which facilitates retrospective chart reviews of our entire health system (institutional review board no. 1538127) (12,13). Using a cohort interrogation tool, i2b2, current procedural terminology codes 225.1 and D33.3 (benign intracranial tumors) were used to identify patients in our health system seen by the neurotology service between January 2009 and December 2019.…”
Section: Data Sourcementioning
confidence: 99%